A new era for the rights of the child: the new “Rome strategy” (2022-2027): The Council of Europe Convention on the Protection of Children against Sexual Exploitation and Sexual Abuse: “The Lanzarote Convention” as an instrument of protection - Espino García , Soraya (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The significant increase in the existence and exploitation of self-generated sexual images and videos by boys and girls, is the focus of the new monitoring Report presented by the Council of Europe´s Lanzarote Committee in Rome. In 2017, exploitation of boy and girls self-generated sexual material was already perceived as a potentially serious risk. Later, in 2019-2020, a large increase in the existence of sexual material generated by minors was observed. The pandemic situation derived from Covid-19 exacerbated this reality. The Report examines 43 European States Parties to The Lanzarote Convention, with special mention to the fact of preventing this particular form of sexual exploitation of boys and girls, investigating and prosecuting it, improving the identification and protection of victims and and likewise, an improvement of the framework law in this matter with the consequent guidelines to the respective governments.